Analisis Financial Technology dan E-Commerce dalam Pengembangan Usaha Mikro Kecil Menengah (UMKM) Food and Beverage di Kabupaten Bogor - Norma Islami; Siti Purnama Sari (Economic Reviews Journal, 2025)
This research aims to analyze the impact of Financial Technology (Fintech) and E-commerce on the development of Micro, Small and Medium Food and Beverage Enterprises in Bogor Regency. Qualitative methods with interview techniques were used to collect data. The research results show that Fintech and E-commerce can increase the effectiveness of business development, income and market reach of Food and Beverage in Bogor Regency. However, several challenges are still faced in implementing this technology. It is hoped that this research can contribute to the development of Food and Beverage in Bogor Regency and become a reference for the government and other stakeholders in making policies that support development.